PENGARUH KEMAMPUAN BERKOMUNIKASI, MOTIVASI BERPRESTASI DAN HASIL UJI KOMPETENSI TERHADAP KINERJA GURU SMK NEGERI DI KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research is aimed: 1) to describe the influence of communication competence partially toward teachers’ performance of State Vocational High Schools in Magelang Regency, 2) to describe the influence of teachers achievement motivation partially toward teachers’ performance of State Vocational High Schools in Magelang Regency, 3) to describe the influence of teachers competence test partially toward teachers’ performance of State Vocational High Schools in Magelang Regency and 4) to describe the influence of communication competence, achievement motivation and teachers competence test simultaneously toward teachers’ performance of State Vocational High Schools in Magelang Regency.This research belongs to a quantitative research. The sampling method used is total sampling of 46 professional certified teachers of State Vocational High School in Magelang Regency. The data of communication competence and achievement motivation are collected through questionnaire, while the data of teachers competence test and teachers’ performance assessment are taken from study of document. The data collected are explained partially and simultaneously to describe the influences toward the determined variables.The results of this research are : 1) the communication competence does not influence teachers’ performance of State Vocational High Schools in Magelang Regency, 2) achievement motivation does not influence teachers’ performance of State Vocational High Schools in Magelang Regency, 3) teachers competence test influence teachers’ performance of State Vocational High Schools in Magelang Regency and 4) based on F-Test it can be concluded that communication competence, achievement motivation and teachers competence test influence toward teachers’ performance of State Vocational High Schools in Magelang Regency.